LEADER'S SELF-SACRIFICE: AN INVESTIGATION IN TERMS OF EMPLOYEES EXTRA-ROLE BEHAVIOR AND ORGANIZATIONAL IDENTIFICATION (Third Sector Social Economic Review, 2024)
This study investigates the effect of leader self-sacrifice on employees’ extra-role behaviors and the mediating role of organizational identification in this effect. In this study, it was assumed that the leader's self-sacrifice, one of the group-oriented leader behaviors, would affect the employees' self-perception and ensure their identification with the organization, enabling them to show extra effort and performance for the organization. To this end, the data were collected from 211 employees working in a chain business operating in the food industry. The model of the research was tested with path analysis. The findings demonstrate that the leader's self-sacrifice could positively predict extra-role behavior and that organizational identification mediates the relationship between leader self-sacrifice and employees' extra-role behavior. Additionally, the instrumentality test revealed that leader self-sacrifice enhancement could positively predict employees' extra-role behavior directly and indirectly through organizational identification.
Keywords: Extra-role behavior; leader; self-sacrificing behavior; organizational identification